Editorial: The "Bashing" of Education Research - Johan Forsell; Lina Rahm; Elisabeth Tenglet; Simon Wessbo (Linköping University Electronic Press, 2018)
For this special issue on the Bashing of Educational Research, we invited contributers from sholars wiht various disciplinary backgrounds to debate contemporary and historical issues in relation to contemporary public critique of education, edicational research, knowledge production, pedagogy, didactic, philosophy and politics.